Neutropenia during HIV Infection: Adverse Consequences and Remedies. (2nd November 2014) - Shi, Xin; Sims, Matthew D; Hanna, Michel M; Xie, Ming; Gulick, Peter G; Zheng, Yong-Hui; Basson, Marc D; Zhang, Ping
<x xml:space="preserve">Abstract</x> Neutropenia frequently occurs in patients with Human immunodeficiency virus (HIV) infection. Causes for neutropenia during HIV infection are multifactoral, including the viral toxicity to hematopoietic tissue, the use of myelotoxic agents for treatment, complication with secondary infections and malignancies, as well as the patient's association with confounding factors which impair myelopoiesis. An increased prevalence and severity of neutropenia is commonly seen in advanced stages of HIV disease. Decline of neutrophil phagocytic defense in combination with the failure of adaptive immunity renders the host highly susceptible to developing fatal secondary infections. Neutropenia and myelosuppression also restrict the use of many antimicrobial agents for treatment of infections caused by HIV and opportunistic pathogens. In recent years, HIV infection has increasingly become a chronic disease because of progress in antiretroviral therapy (ART). Prevention and treatment of severe neutropenia becomes critical for improving the survival of HIV-infected patients.